2015
DOI: 10.1007/s00726-015-2031-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic oral l-arginine administration on the l-arginine/NO pathway in patients with peripheral arterial occlusive disease or coronary artery disease: l-Arginine prevents renal loss of nitrite, the major NO reservoir

Abstract: Despite saturation of nitric oxide (NO) synthase (NOS) by its substrate L-arginine (Arg), oral and intravenous supplementation of Arg may enhance NO synthesis, a phenomenon known as "The L-arginine paradox". Yet, Arg is not only a source of NO, but is also a source for guanidine-methylated (N (G)) arginine derivatives which are all inhibitors of NOS activity. Therefore, Arg supplementation may not always result in enhanced NO synthesis. Concomitant synthesis of N (G)-monomethyl arginine (MMA), N (G),N (G)-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 52 publications
0
27
0
1
Order By: Relevance
“…Especially, intravenous administration of the carbonic anhydrase (CA) inhibitor acetazolamide to conscious rats increased UNOx by a factor of almost 3, strongly suggesting involvement of renal CA in the handling of nitrate/nitrite excretion/reabsorption (Sütö et al 1995). In humans, we have recently shown that renal CA isoforms are involved in the reabsorption of inorganic nitrite (NO2 -) and to a lesser extent of inorganic nitrate (ONO2 -) (Tsikas and Chobanyan-Jürgens 2010; Chobanyan-Jürgens et al 2012a;Tsikas et al 2014;Schneider et al 2015). This newly discovered role of renal CA isoforms is of particular importance, because nitrite is an important and abundant reservoir of NO in tissues and cells including erythrocytes (Gladwin et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, intravenous administration of the carbonic anhydrase (CA) inhibitor acetazolamide to conscious rats increased UNOx by a factor of almost 3, strongly suggesting involvement of renal CA in the handling of nitrate/nitrite excretion/reabsorption (Sütö et al 1995). In humans, we have recently shown that renal CA isoforms are involved in the reabsorption of inorganic nitrite (NO2 -) and to a lesser extent of inorganic nitrate (ONO2 -) (Tsikas and Chobanyan-Jürgens 2010; Chobanyan-Jürgens et al 2012a;Tsikas et al 2014;Schneider et al 2015). This newly discovered role of renal CA isoforms is of particular importance, because nitrite is an important and abundant reservoir of NO in tissues and cells including erythrocytes (Gladwin et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical investigations on these Arg metabolites in adults extend their key importance to other diseases in adults, including multiple sclerosis, chronic liver and kidney disease, obesity, rheumatoid arthritis, coronary artery disease, and peripheral arterial occlusive disease (Dimitroulas et al 2015;Frenay et al 2015a, b;Haghikia et al 2015;Kayacelebi et al 2015c;Kruszelnicka et al 2015;May et al 2015;Pilz et al 2015a;Schneider et al 2015;Sitar et al 2015). In childhood and adolescence, the significance of ADMA or hArg as cardiovascular risk factors is little investigated and incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The circulating concentration of ADMA in healthy children is more than two times higher than in healthy adults (Lücke et al 2007), suggesting that ADMA and presumably the whole Arg/NO pathway greatly differ between children/adolescents and adults, i.e., that children are not small adults. In the present work, emphasis was given to the Arg/NO pathway, including hArg in healthy children and adolescents, as well as in those suffering from type 1 diabetes mellitus, Duchenne muscular dystrophy, and growth hormone deficiency (GHD) (Carmann et al 2015;Hörster et al 2015;Langen et al 2015; see also Thum et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under pathological conditions, ADMA concentrations significantly rise (3–5 μmol/l) and inhibit synthesis of NOS and NO, which leads to diastolic function depression of peripheral vascular and decreased cerebral blood perfusion [10,11]. Research shows that L-arginine-NO synthetic obstacles have a close relationship with hypertension and atherosclerosis [12,13]. In vivo , ADMA expression levels have obvious correlation with the occurrence and prognosis of acute cardiovascular and cerebrovascular diseases [14].…”
Section: Introductionmentioning
confidence: 99%